Brain cortex activity in children with anterior open bite. (2017)
Anterior Open Bite (AOB) is a malocclusion, associated with alterations in tongue´s position and/or function, which are highly regulated by the brain cortex. The aims of this study were to determine the activity of the brain cortex of children with AOB at rest and during phonation and deglutition.